PELATIHAN ENTREPRENEURSHIP DALAM MEMBANGUN JIWA WIRAUSAHA BAGI PIKK PLN IP-SURALAYA PGU - Tabroni Tabroni; Mamay Komarudin; Aria Cendana Kusuma; Irma Nurmala Dewi (Gapenas Publisher, 2021)
The purpose of implementing this Community Service program is to provide insight into the knowledge and skills of local employees related to entrepreneurship, which can be used to show soft skills in the workplace or as a side-job outside of daily activities. This activity is carried out by providing training that includes: lectures, discussions and simulations of business planning. The targets and partners of this PKM are Lecturers of Bina Bangsa University and employees of PIKK PLN IP-Suralaya PGU who want to become business actors. The implementation of PKM activities carried out has been carried out by the agreed plan, but the implementation process still needs to be done continuously to implement the PKM program. This program has a sustainable impact on preparing advanced and independent employees